2022
DOI: 10.3390/ijerph19063504
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Post-Traumatic Stress Disorder and the Sense of Gains and Losses during the COVID-19 Pandemic: An International Study

Abstract: This study was primarily designed to investigate the perception of changes in selected areas of life experienced by adults of various nationalities in connection to the long-lasting COVID-19 pandemic. The second objective was to identify the factors increasing the risk of perception of negative changes in life during the pandemic. The tools applied in the study include a self-report questionnaire designed to measure sociodemographic data and health status of the subjects, COVID-19 Sense of Life Changes Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…A lack of evidence-based treatment options and the unpredictability of recovery further worsened their mental health status and contributed to increased feelings of frustration and helplessness. These findings are broadly consistent with those found in previous studies that COVID-19 survivors and those experiencing long COVID were more likely to have worsening mental health issues and quality of life ( 31 35 ). As the COVID-19 pandemic continues into its third year, long COVID has gained increasing recognition worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…A lack of evidence-based treatment options and the unpredictability of recovery further worsened their mental health status and contributed to increased feelings of frustration and helplessness. These findings are broadly consistent with those found in previous studies that COVID-19 survivors and those experiencing long COVID were more likely to have worsening mental health issues and quality of life ( 31 35 ). As the COVID-19 pandemic continues into its third year, long COVID has gained increasing recognition worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…A significant association was found between the miscarriage or stillbirth in the participants' history and the mean score they achieved on the PTSD scale. Examining data from two population-based cross-sectional studies, Szepietowska et al found that pregnancy loss and risk for psychiatric disorders increased in their study (12). In addition, earlier pregnancy loss has been shown to negatively affect mood and psychological well-being, particularly in young women (13).…”
Section: Discussionmentioning
confidence: 97%
“…There was also a change in the emotional representation of the disease. Initial increase in negative emotions [23,31] was followed with a slight decrease in the negative perceptions of COVID-19 [4], and even with a sense of positive changes in life [32]. However, a meta-analysis [33] of research reports focusing on mental health during the COVID-19 pandemic showed that stress and mental burden in this case were comparable to war time experiences.…”
mentioning
confidence: 91%